Global bioethics and implementation of its principles in the criminal legislation of the countries of the continental law family - Trynova, Ya. O.; Anishchenko, M. A.; Kyrbiatiev, O.; Zelenskyi, Ye.; Karpenko, A.; Аніщенко, Михайло Анатолійович (My University, 2023)
The current criminal law of Ukraine and some other countries families of continental law, which include some countries of the post-Soviet space (Azerbaijan, Estonia, Lithuania, Moldova and others) does not fully fulfill the tasks formulated in it, that is, it is not legal in its essence, and therefore it cannot fully and effectively implement the legal protection of the rights and freedoms of human and citizen, accordingly – it cannot fulfill the main task: legal provision of safety of society’s existence. The purpose of the article is to develop and propose the use of a new approach in law-making in the field of modern criminal law of the countries of the continental law family: the formulation and introduction into scientific circulation of the principles of bioethics as the dominant branch of criminal law and their implementation in theoretical models of relevant criminal law and some other norms.
Keywords: Bioethics; Criminal Law; criminal legislation; natural law; neo jusnaturalism; law-making; continental legal family